2015
DOI: 10.1007/s00246-015-1110-z
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Comparison of Dexmedetomidine Versus Midazolam for Pediatric Patients with Congenital Heart Disease Requiring Postoperative Sedation

Abstract: We hypothesized that postoperative sedation with dexmedetomidine/fentanyl would be effective in infants and neonates with congenital heart disease and pulmonary arterial hypertension (PAH). Children who were <36 months of age, had congenital heart disease with PAH, and had been treated at our hospital between October 2011 and April 2013 (n = 187) were included in this retrospective study. Either dexmedetomidine/fentanyl (Group Dex) or midazolam/fentanyl (Group Mid) was used for postoperative sedation. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Of the remaining 28 eligible studies, 14 were removed because they reported on other outcomes, they were not full-text, or two publications used the same patients. Fourteen studies were included in the final meta-analysis (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The selection process is detailed in Figure 1.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the remaining 28 eligible studies, 14 were removed because they reported on other outcomes, they were not full-text, or two publications used the same patients. Fourteen studies were included in the final meta-analysis (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The selection process is detailed in Figure 1.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…All of the studies were published from 2006 to 2015; the sample sizes ranged from 14 to 1088, and the total number of patients was 2229 (dexmedeto-midine group, n = 1055; control group, n = 1174). Five of the included studies were RCTs (20)(21)(22)(23)(24), one was a post hoc analysis of RCTs (25), and the remaining eight were cohort studies (26)(27)(28)(29)(30)(31)(32)(33): four retrospective (26,29,30,33) and four prospective (27,28,31,32).…”
Section: Article Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Other studies showed that the use of dexmedetomidine is safe in patients with congenital heart diseases and in the post-operatory of cardiac surgery without hypotension and bradycardia harmful to the patient. [49][50][51][52][53] Management of abstinence syndrome Prolonged administration of opioids and/or benzodiazepines leads to tolerance. Rapid suspension of these medications implicates a myriad of signs and symptoms, called abstinence syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…The results of a meta-analysis that compared use of dexmedetomidine with placebo or other alternative anesthetic agents during pediatric congenital heart disease surgery suggested that dexmedetomidine was associated with shorter length of mechanical ventilation, lower post-operative fentanyl and morphine requirements, reduced stress response, and lower risk of delirium (Pan et al, 2016 ). Similarly, in a retrospective comparison in pediatric patients with congenital heart disease requiring post-operative sedation, patients who received dexmedetomidine required significantly lower doses of adjunctive sedative/analgesic drugs compared with those who received midazolam (Jiang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%